A SOCIOLINGUISTIC ANALYSIS OF CODE MIXING USAGE AMONG GENERATION Z AT MUHAMMADIYAH UNIVERSITY OF TANGERANG - Sintia, Desmi Ayu; Alyani, Elsa; Saepudin, Novi Cintya; Putri, Riana Andriani; Nargis, Nargis (Media Inovasi Pendidikan dan Publikasi, 2025)
This research discusses the phenomenon of code mixing among Generation Z, especially students of Universitas Muhammadiyah Tangerang, as a form of dynamic communication influenced by social media and technological developments. Using qualitative methods, data was collected through questionnaires and Instagram content analysis. The results showed that 87.5% of respondents felt that code-mixing increased the relevance of their content on Instagram, and 93.8% believed that this practice made it easier to convey messages. In addition, 68.8% of respondents considered code-mixing to be “cool” and reflective of their bilingual identity. These findings confirm that code-mixing functions not only as a communication tool, but also as a symbol of creativity and social identity, as well as adaptation to the global context. In conclusion, Generation Z's use of code-mixing reflects the evolving flexibility of language, influenced by social, cultural and technological changes, and strengthens social connections in the digital age.